Long dsRNA but not siRNA initiates RNAi in western corn rootworm larvae and adults. (17th April 2015) - Li, H.; Khajuria, C.; Rangasamy, M.; Gandra, P.; Fitter, M.; Geng, C.; Woosely, A.; Hasler, J.; Schulenberg, G.; Worden, S.; McEwan, R.; Evans, C.; et al.
Abstract Transgenic maize plants expressing dsRNA targeting western corn rootworm (WCR, Diabrotica virgifera virgifera LeConte) v‐ATPase subunit C mRNA for RNAi provided significant root protection from WCR larval feeding damage in greenhouse assays compared to negative controls. Transcribed hairpin dsRNA in WCR‐resistant maize plants was present as both intact hairpin‐derived dsRNA and plant‐processed siRNA. Therefore, the ability of dsRNA and siRNA targeting Dv v‐ATPase CmRNA to cause an RNAi response was studied in both WCR larvae and adults. In 9‐day diet‐based feeding assays, dsRNA of at least 60 bp in length resulted in high levels of larval mortality. In contrast, 15‐, 25‐ or 27‐bp dsRNAs or pooled 21‐bp siRNAs did not cause mortality of exposed larvae. When larvae were fed with diet overlaid with siRNAs, Dv v‐ATPase C transcript levels did not change. Conversely, when WCR larvae were fed with diet overlaid with 184‐bp dsRNA, the mRNA level was reduced by >20‐fold relative to yfp dsRNA negative control. Similarly, 184‐bp dsRNA caused 100% mortality of WCR adults, whereas the mortality of adults fed on diet treated with siRNAs was similar to the negative control. Feeding adults with siRNAs on diet did not affect the level of Dv v‐ATPase CmRNA transcripts, whereas adults fed with the 184‐bp dsRNA showed approximately 35‐fold reduction in the target mRNA level. Similar results were obtained with the WCR adults injected with 184‐bp dsRNA or 21‐bp siRNA. These results suggest that only long dsRNA or hairpin‐derived dsRNA is effective in causing lethal knock‐down of Dv v‐ATPase CmRNA. These results have implications for efficacious plant‐delivered dsRNA for the protection of transgenic maize from WCR feeding damage and for the risk assessment of transgenic maize expressing insecticidal dsRNA.